Novel TBL1XR1, EPHA7 and SLFN12 mutations in a Sezary syndrome patient discovered by whole exome sequencing. Issue 5 (May 2014) - Andersson, Emma; Eldfors, Samuli; Edgren, Henrik; Ellonen, Pekka; Väkevä, Liisa; Ranki, Annamari; Mustjoki, Satu
Abstract Sezary syndrome (SS) is an aggressive leukaemic variant of cutaneous T‐cell lymphoma. Recurrent chromosomal aberrations have been found in SS, but the whole genetic mutation spectrum is unknown. To better understand the molecular pathogenesis of SS, we performed exome sequencing, copy number variation (CNV) and gene expression analysis of primary SS cells. In our index patient with typical SS, we found novel somatic missense mutations in TBL1XR1, EPHA7 and SLFN12 genes in addition to larger chromosomal changes. The mutations are located in biologically relevant genes affecting apoptosis and T‐cell maturation. They may play a role in the pathobiology of the disease, but no recurrent mutations were discovered in nine additional patients with SS studied. Thus, screening of larger patient cohorts is needed to confirm their prevalence and biological significance in SS.